Antibacterial oral natives: Studies in the Faculty of Odontolgy of the National Major University of San Marcos - Moromi, Hilda (2009)
Dental caries is a disease that affects 95 % of the human population. One of the mechanisms to prevent it in modern times, is the use of natural substances, specially those thatconbin polyphenols: 1) like a simple infusion, 2) after a boiled time, and 3) like an extract after a chemical process. They also have advantages such as easy access and management, low cost and, most of all, few undesirable side effects. In the Faculiy of Odontolegy of the National Major University of San Marcos, several studies have been carried out in vitro and in vivo. They were analyzed to search for evidence in order to show actual tendencies to possible application for a final solution: dental caries. Final conclusions are: 1) In vitro studies, there are evidences of the anti-bacteria1 effect of the natural principles (Propóleo novogranatense Erythroxylum, Minthostachys mollis, Camellia sinensis and Croton lachleri extracts) for the oral flora. Also, anti-bacteria1 effect was not observed with: Aloe vera and Uncaria tornientosa. 2) In vitro studies, Camellia sinensis has demonstrated capacity to avoid bacteria1 plaque formation. 3) In vivo study, Camellia sinensis in colutorio showed oral anti-bacteria1 effect up to 30 minutes after mouthwash.